Correction Procedure of Wave Signals for a Viscoelastic Split Hopkinson Pressure Bar - Jacek JANISZEWSKI; Witold BUŻANTOWICZ; Paweł BARANOWSKI (Problemy Mechatroniki)
A polymeric split Hopkinson pressure bar technique (SHPB) is preferred for testing materials with low mechanical impedance. However, the use of polymeric bars requires additional analysis for data reduction, temperature complications and additional restrictions compared with traditional metallic pressure bars. A viscoelastic material, such as PMMA, exhibits both wave attenuation and wave dispersion. When a wave travels through a polymer bar, the wave amplitude decreases due to attenuation and the wave shape becomes distorted. Therefore, signals measured at given positions on a viscoelastic bar do not represent the pulse at another position along the pressure bar without complex corrections. This paper is concerned with the problem of correction of dispersion and attenuation of waves in the viscoelastic SHPB. It has been demonstrated that the Fast Fourier Transform (FFT) spectral analysis method used to reconstruct wave profiles on the measured signals which are being distorted by wave attenuation and dispersion effects is valid and allows for obtaining satisfactory results for tire rubber.